Wpływ polityki informacyjnej NBP na międzybankowy rynek lokat w latach 2003-2004 - Dziwok, Ewa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Since 1998 NBP have adopted a monetary policy approach which is generally described as "inflation targeting". Following Bernanke, inflation targeting is characterised by the public announcement of official quantitative targets (or target ranges) for the inflation rate for one or more time horizons and good communication with the public about plans and objectives of monetary authorities. In opinion of most Polish economists most decision of RPP surprise the market and make it less stable.The main goal of this article is to show the influence of central bank signals during two years, between 2003 and 2004. By using multiple regression with three explanatory variables: an official rate of 14-days NBP-bills (open market operation), monetary policy restriction's level and monetary policy speeches it can examine how various monetary policy signals affect term structure of interest rate. The longer interest rate is the stronger and more important are RPP speeches.This article concludes that NBP communication plays an essential role in Polish monetary policy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 145-153